IMPROVING COMMUNICATION SKILLS THROUGH WHATSAPP GROUP MEDIA - Tuti Asih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
During the Covid-19 pandemic, the government implemented a learning system that must meet health protocols. The school decided to hold learning from home so that it required teachers to be creative in presenting the learning materials. One of them was by utilizing the whatsapp group learning media which enabled the teachers to present materials, guide learning activities, and evaluate the learning. This research method was a classroom action research conducted at grade V SDN 002 Sungai Salak. The instrument used was the observation sheet of students' communication skills. The results showed that there was a good increase in students' communication skills through whatsapp. It was revealed that the average percentage of students' communication skills in Cycle I was 67.01% and it increased in Cycle II to 73.78%. This research concluded that the use of WhatsApp application improved the students’ communication skills.